Gender Differences of Schizophrenia Patients With and Without Depressive Symptoms in Clinical Characteristics - Liu, Ruimei; Fang, Xinyu; Yu, Lingfang; Wang, Dandan; Wu, Zenan; Guo, Chaoyue; Teng, Xinyue; Ren, Juanjuan; Zhang, Chen (Frontiers in Psychiatry, 2022)
Objectives: To investigate the differences in psychotic symptoms and cognitive function in schizophrenics with and without depression and to compare gender differences in the correlation between depressive symptoms and clinical characteristics in those patients. Methods: A total of 190 schizophrenia patients and 200 healthy controls were recruited in the study. We used the Positive and Negative Symptom Scale (PANSS), the Calgary Depression Scale for Schizophrenia (CDSS) and the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) to evaluate the psychiatric symptoms, depressive symptoms and cognitive function, respectively. Patients with CDSS score ≥7 were divided into depression group, and CDSS < 7 was viewed as without depression. Results: Patients with schizophrenia had lower total scores of RBANS and 5 subscale (immediate memory, visual span, verbal function, attention, and delayed memory) scores compared to healthy controls. In the case group, patients who concomitant with depression had higher PANSS scores (Ps < 0.001) and lower RBANS (Ps < 0.05) scores than those without depression. After gender stratification, PANSS total scores and subscale scores were significantly different between schizophrenics with and without depressive symptoms in both male and female groups (Ps < 0.001). For cognitive function, there were significant differences in RBANS total score and subscale score except attention between female patients with and without schizophrenia but not in male schizophrenia patients. Furthermore, the correlation analysis showed that the total CDSS score was positively correlated with PANSS score (P < 0.001) and RBANS score in male and female groups (male: P = 0.010, female: P = 0.001). Conclusion: Our findings provided evidence supporting the gender differences in psychiatric symptoms and cognitive function between schizophrenia patients with and without depressive symptoms.